2016
DOI: 10.1177/1098611116653398
|View full text |Cite
|
Sign up to set email alerts
|

Officer Perceptions of Body-Worn Cameras Before and After Deployment

Abstract: Over the past few years, several events have highlighted the strained relationship between the police and residents in many communities. Police officer body-worn cameras (BWCs) have been advocated as a tool by which police-community relations can be strengthened, while simultaneously increasing transparency and accountability of police departments. Support for BWCs from the public and federal government is strong, and some studies have examined police perceptions of BWCs. However, comparisons of officer percep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
200
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(217 citation statements)
references
References 16 publications
13
200
0
4
Order By: Relevance
“…For example, the Boston police union attempted to stop the department's BWC program through a federal injunction (Levenson and Allen, ). Gaub et al.’s () comparison of officer perceptions shows that Phoenix police officers were less supportive of BWCs than were officers in neighboring Tempe or Spokane. Moreover, Katz et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the Boston police union attempted to stop the department's BWC program through a federal injunction (Levenson and Allen, ). Gaub et al.’s () comparison of officer perceptions shows that Phoenix police officers were less supportive of BWCs than were officers in neighboring Tempe or Spokane. Moreover, Katz et al.…”
Section: Discussionmentioning
confidence: 99%
“…White, Todak, and Gaub (2017) found a connection between citizen awareness of a BWC and citizen perceptions of procedural justice. The findings from several studies have demonstrated high levels of both officer (Gaub, Choate, Todak, Katz, and White, 2016;Jennings, Fridell, and Lynch, 2014;Mesa Police Department, 2013) and citizen support for BWCs (Crow, Snyder, Crichlow, and Smykla, 2017;Morin, Parker, Stepler, and Mercer, 2017;Sousa et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The existing evidence on whether BWCs have the anticipated effects on policing outcomes remains relatively limited (17)(18)(19). Several observational studies have evaluated BWCs by comparing the behavior of officers before and after the introduction of BWCs into the police department (20,21). Other studies compared officers who happened to wear BWCs to those without (15,22,23).…”
mentioning
confidence: 99%
“…He argues that the use of algorithms can also be utilized to flag at-risk officers for complaints and improper conduct. While Ferguson claims field officers and police unions will likely push back against these new mechanisms of oversight, at least one recent research study indicates police officers may not be opposed to these practices (Gaub et al 2016).…”
mentioning
confidence: 99%